2023
DOI: 10.1111/cbdd.14249
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel class inhibitors of NSD3 methyltransferase showing a unique, bivalent binding mode in the SET domain

Abstract: NSD3/WHSC1L1 lysine methyltransferase promotes the transcription of target genes through di‐ or tri‐methylation at histone H3K36 using SAM as a cofactor. Genetic alterations such as amplification and gain‐of‐function mutation of NSD3 act as oncogenic drivers in several cancers including squamous cell lung cancer and breast cancer. NSD3 is an important therapeutic target for cancers, but the reported NSD3 inhibitors targeting the catalytic SET domain are very rare and show a poor activity. Herein, from a virtua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…These studies correlate with our findings that NSD3S/MYC interaction stabilizes and activates MYC transcriptional activity. Finally, Kim et al, reported the identification of a new NSD3 inhibitor which targets the SET domain of the protein, therefore only the NSD3L isoform [86]. However, based on the understanding we have regarding the function of NSD3, particularly NSD3S, we believe that inhibitors targeting both isoforms would be more effective in blocking oncogenic programs, in a therapeutic context.…”
Section: Discussionmentioning
confidence: 99%
“…These studies correlate with our findings that NSD3S/MYC interaction stabilizes and activates MYC transcriptional activity. Finally, Kim et al, reported the identification of a new NSD3 inhibitor which targets the SET domain of the protein, therefore only the NSD3L isoform [86]. However, based on the understanding we have regarding the function of NSD3, particularly NSD3S, we believe that inhibitors targeting both isoforms would be more effective in blocking oncogenic programs, in a therapeutic context.…”
Section: Discussionmentioning
confidence: 99%
“…These studies correlate with our findings that NSD3S/MYC interaction stabilizes and activates MYC transcriptional activity. Finally, Kim et al reported the identification of a new NSD3 inhibitor which targets the SET domain of the protein, therefore only the NSD3L isoform [87]. However, based on the understanding we have regarding the function of NSD3, particularly NSD3S, we believe that inhibitors targeting both isoforms would be more effective in blocking oncogenic programs in a therapeutic context.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibitors of H3K36 methyltransferases could also act as potential drugs to control satellite expression in prostate cancer. H3K36 methyltransferases are known to act as cancer drug targets, and their inhibitors are under development [54][55][56]. Besides histone modifying enzymes that regulate the epigenetic state of heterochromatin, endonuclease Dicer1 is also known to control satellite transcript levels.…”
Section: Hypothesis: How To Stabilize Satellite Dna Transcription And...mentioning
confidence: 99%